154k views
2 votes
hich function in vertex form is equivalent to f(x) = x2 + 6x + 3? f(x) = (x + 3)2 + 3 f(x) = (x + 3)2 − 6 f(x) = (x + 6)2 + 3 f(x) = (x + 6)2 − 6

1 Answer

3 votes
f(x) = (x + 3)2 − 6

You can find the vertex by looking for -b/2a which is equal to -3 and then finding the corresponding y value, which is -6. Then use those numbers in vertex form, which is what we see in the answer above.
User Parth Mehta
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.